MEAN PLATELET VOLUME IN TYPE II DIABETES MELLITUS, CASE CONTROL STUDY – GEZIRA CENTRAL SUDAN - Ali, Soad Fadlallah; Ali, Omar Widaa (Gezira Journal of Health Sciences, 2010)
Aim: Thrombotic disorders are the major complications of diabetes mellitus (DM). Platelets are considered to play a role in these vaso-occlusive complications. The mean platelet volume (MPV) is recently taken as indicator for platelet reactivity. The aim of this study was to show the state of platelet activity in type II diabetes mellitus by indication of MPV. Methods: This study was done in Wad Madani, Gezira State, Sudan 2007.   MPV was measured in 100 adult type II diabetic Sudanese patients and 100 adult healthy control subjects matched for age and gender.  Results: MPV was found to be significantly higher among the diabetic group (mean 9.9 fl) than the control group (mean 9.0 fl) (P value 0.015). Conclusion: We conclude that elevated MPV may indicate platelet hyperactivity, which may contribute to the vascular complications of type II DM.